Employee Performance in Yogyakarta: Comparison Between Saturday Workdays and Saturday Holidays - Yunus Agung Kristanto; Fajar Eryanto Septiawan Septiawan (ICON Publisher, 2025)
Employee performance is a crucial factor in enhancing organizational productivity, and work schedule arrangements, including working on Saturdays, are becoming increasingly important. This study aims to evaluate the performance comparison between employees who work on Saturdays and those who are off on that day in Yogyakarta. The method used is an independent sample t-test to analyze the performance differences between the two groups. The results show that employees who are off on Saturdays have significantly better performance with an average score of 86.51 compared to 72.49 for those who work, with a p-value < 0.001. The conclusion of this study emphasizes the importance of work policies that consider work-life balance to improve employee productivity. These findings provide new insights for management in designing more effective and sustainable work policies and open up opportunities for further research on factors affecting employee performance in a broader context.